Location and characteristics of ribosomal protein binding sites in the 16S RNA of Escherichia coli. - Zimmermann, R A (1975)
Specific binding sites for five proteins of the Escherichia coli 30S ribosomal subunit have been located within the 16S RNA. The sites are structurally diverse and range in size from 40 to 500 nucleotides; their functional integrity appears to depend upon both the secondary structure and conformation of the RNA molecule. Evidence is presented which indicates that additional proteins interact with the RNA at later stages of subunit assembly.